Nitrogen balance along a northern boreal forest fire chronosequence - Palviainen, Marjo; Pumpanen, Jukka; Berninger, Frank; Ritala, Kaisa; Duan, Baoli; Heinonsalo, Jussi; Sun, Hui; Koster, Egle; Köster, Kajar (PLOS ONE, 2017)
Fire is a major natural disturbance factor in boreal forests, and the frequency of forest fires is predicted to increase due to climate change. Nitrogen (N) is a key determinant of carbon sequestration in boreal forests because the shortage of N limits tree growth. We studied changes in N pools and fluxes, and the overall N balance across a 155-year non stand replacing fire chronosequence in sub-arctic Pinus sylvestris forests in Finland. Two years after the fire, total ecosystem N pool was 622 kg ha(-1) of which 16% was in the vegetation, 8% in the dead biomass and 76% in the soil. 155 years after the fire, total N pool was 960 kg ha(-1), with 27% in the vegetation, 3% in the dead biomass and 69% in the soil. This implies an annual accumulation rate of 2.28 kg ha(-1) which was distributed equally between soil and biomass. The observed changes in N pools were consistent with the computed N balance +2.11 kg ha(-1) yr(-1) over the 155-year post-fire period. Nitrogen deposition was an important component of the N balance. The biological N fixation increased with succession and constituted 9% of the total N input during the 155 post-fire years. N2O fluxes were negligible (<0.01 kg ha(-1) yr(-1)) and did not differ among post-fire age classes. The number and intensity of microbial genes involved in N cycling were lower at the site 60 years after fire compared to the youngest and the oldest sites indicating potential differences in soil N cycling processes. The results suggest that in sub-arctic pine forests, the non-stand-replacing, intermediate severity fires decrease considerably N pools in biomass but changes in soil and total ecosystem N pools are slight. Current fire-return interval does not seem to pose a great threat to ecosystem productivity and N status in these sub-arctic forests. Peer reviewed